Analisis penghindaran pajak (tax avoidance) perusahaan multinasional (studi kasus pt adaro energy tbk) - Wahyuningtias, Tri; Athariq, Salsabila Phytagora; Nurkhasanah, Kharisma Ika; Wahdini, Siti Aliza Nuraini; Fasya, Yulianisa Amelia; Janah, Rahil Syira Roudhlotul (University of Merdeka Malang, 2025)
This study discusses the practice of tax avoidance through transfer pricing carried out by multinational companies, with a focus on the case of PT Adaro Energy Tbk. The aim of this research is to analyze the transfer pricing mechanism between PT Adaro Energy Tbk and its subsidiaries in Singapore, which has the potential to cause losses in state revenues. The research method used is qualitative, examining legal aspects, tax regulations and the application of the arm's length principle. The research results show that PT Adaro is suspected of carrying out transfer pricing by selling coal to its subsidiaries in Singapore at prices lower than the market price. The subsidiary then resells the coal at a higher price, so that profits are shifted to jurisdictions with low tax rates. This practice exploits loopholes in the transfer pricing system and has a negative impact on Indonesian tax revenues. The Directorate General of Taxes (DJP) responded by making corrections based on Article 18 of the Income Tax Law and PMK No. 213/PMK.03/2016, which regulates the method for determining fair prices. This research also evaluates the effectiveness of Indonesian tax laws in facing the challenge of tax avoidance and provides recommendations for improving tax compliance of multinational companies. It is hoped that this research can contribute to strengthening tax regulations in Indonesia and encourage the application of the arm's length principle in transactions between affiliated companies.